2014
DOI: 10.1038/nphys2907
|View full text |Cite
|
Sign up to set email alerts
|

Origins of bad-metal conductivity and the insulator–metal transition in the rare-earth nickelates

Abstract: For most metals, increasing temperature (T) or disorder hastens electron scattering. The electronic conductivity (σ ) decreases as T rises because electrons are more rapidly scattered by lattice vibrations. The value of σ decreases as disorder increases because electrons are more rapidly scattered by imperfections in the material. This is the scattering rate hypothesis, which has guided our understanding of metal conductivity for over a century. However, for so-called bad metals with very low σ this hypothesis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
129
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(144 citation statements)
references
References 39 publications
14
129
1
Order By: Relevance
“…18,19 The Drude spectral weight is redistributed up to at least 5 eV when the system becomes insulating, [18][19][20] which was interpeted as an indication of Mott physics 19 or effects of electron-phonon interaction. 20 However, a clear mechanism of the optical response of the insulating phase has thus far been lacking.…”
Section: Methodsmentioning
confidence: 99%
“…18,19 The Drude spectral weight is redistributed up to at least 5 eV when the system becomes insulating, [18][19][20] which was interpeted as an indication of Mott physics 19 or effects of electron-phonon interaction. 20 However, a clear mechanism of the optical response of the insulating phase has thus far been lacking.…”
Section: Methodsmentioning
confidence: 99%
“…The doubling of unit cell and combination of Ni 2 þ t 6 2g e 2 g and Ni 4 þ t 6 2g e 0 g render a new band diagram with a Mott-Hubbard splitting involved. Though there is a debate about whether nickelates are Mott-Hubbard insulator 16 , charge-transfer insulator 17 , negative charge-transfer insulator 18 or even band insulator 6 , both theoretical and experimental evidence indicate such band gap of SNO's insulating state is quite small (a few hundred millivolts) because of the mixed character of Ni 2 þ and Ni 4 þ (or Ni (3-…”
Section: Resultsmentioning
confidence: 99%
“…It is in fact observed that in a large number of bad metals the Drude peak in the optical conductivity moves away from ω = 0 as the temperature is increased, leading to a suppression of low frequency spectral weight. This phenomenon is seen in ruthenates [16,17], cobaltates [18,19], cuprates [20][21][22][23][24], vanadates [25,26], manganates [27,28], nickelates [29] and organic conductors [30,31]. The behavior is illustrated in figure 1 below.…”
mentioning
confidence: 94%